Research Trends In Multimodal Critical Discourse Analysis: A Bibliometric Analysis - Nurohmah, Hety; Sundasewu, Rama Ulun (Tamaddun Life, 2024)
This research aims to understand the evolution and development of Critical Discourse Analysis (CDA) research with a focus on multimodality. CDA is an interdisciplinary approach that explores the use of language and discourse in reproducing, reinforcing, and being closely linked to social relations, power, and ideology. From the initial understanding introduced by Norman Fairclough in the 1980s, CDA has become an important tool for analyzing power structures and social constructions in various contexts, including media, politics, education, and popular culture. CDA has undergone significant transformations along with complex changes in the social and political world. This research aims to map the latest trends and developments in CDA studies, with a special focus on aspects of multimodality. The data collection process is carried out by data mining process in Scopus using keywords and search limitations per category Subject area; Doc.type; Pub.stage; Source type; Language. The document data collected were 303 Scopus indexed documents. By involving bibliometric methods through the Vosviewer tool, the data was visualized and analyzed. The results of the study found that the development of CDA research in the aspect of multimodality has increased in number every year. The study of CDA in terms of multimodality began in 1993 and began to experience an increase in the number of studies from 2013 to 2023. The scope of keywords that emerged was six clusters. Each cluster of keywords reflects special attention to the scope in the study of critical discourse analysis and multimodality, including the diversity of research themes, the intersection of media and social aspects, the importance of visual and multimodal analysis, the connection with the local context, and the application of critical theories and concepts.